THE USE OF TRADITIONAL GAME “KABENTE” TO IMPROVE VOCABULARY MASTERY OF SMP NEGERI 1 SIOMPU BARAT - Asti Wahyuni B; Wa Ode Nining Kurnia Gafaruddin; Adelia Adelia (English Education Department, 2021)
Problem in this research was whether the use of traditional game Kabente has a significant effect on students’ vocabulary mastery. While the objective of this research was to know the significance effect of traditional game Kabente n students ocabularymastery at grade VII A SMP Negeri 1 Siompu Barat. This research was pre experimental research. The population of the research were all grade II students of SMPNegeri 1 Siompu Barat which consisted of 3 classes with total 79 students. Sample in this research was taken with random sampling technique. Sample of the research was class VII A consisted of 25 students. Instrument which used in this research was test. Research outcome obtained showed that the mean score in pre-test was 36.36, while in post-test was 80.06. From hypotehis test result by using t test, obtained tcount = 2.54 and obtained significant value 0.00<0.050. therefore, it could be concluded that H0 was rejected and H1 was accepted. Therefore, the application of traditional game Kabente had significant effect on students vocabulary mastery at grade VII students of SMP Negeri 1 Siompu Barat, academic year 2020/2021.